CBE678: Introduction to food science and technology / College of Engineering - UiTM, College of Engineering (2018)
This course covers an introduction to the food processing industry, food constituents, composition and processing of different food commodities, sensory and nutritional aspects, food safety, legislation and quality, packaging of food product and product development in food industries.